Comunicação interna como estratégia de gestão educacional: realidade de uma escola particular confessional de educação básica - Lacerda, Dayse Mara Martins (Universidade do Vale do Rio dos Sinos, 2018)
This work makes public the results of a research-action on internal communication as a strategy to educational management, conducted with employees from a Catholic confessional private school of basic education in Belo Horizonte. The study also shows a proposal of internal communication process built with the participation of the research subjects and suggested to the Principals of the educational unit chosen as empiric field as an intervention project. The motivation for this work was born of the challenge of mobilizing people around a common goal: improving educational quality to transform society. Part of the certainty that teachers and non-teaching professionals are the basic public for qualification of educational processes and for the delivery of the promise of students’ full training, taken up by the school as one of its institutional objectives. It brings as for proposals – the reflection on the importance of internal communication for the mission of a teaching institution, the diagnosis of the situation of internal communication for the social group researched and the identification of points likely to be improved, which go from establishing and explaining institutional policies up to the employment of certain expressions in the content of corporate e-mails. It identifies the limitation of academic research related to the internal communication in Basic Education schools. It is based in a qualitative and quantitative study performed by means of semi-structured interviews directed to a group of professionals from all areas and hierarchic levels, and by an electronic questionnaire applied to the totality of the employees for the construction, based on “empathy maps” and on “value opposition charts” from an intervention proposal which may help to explain and consolidate the internal communication process as a management strategy. As a conclusion, it can be noted that the internal communication issues in the group researched are less technical and are more intimately connected to the management model and leadership styles. Authority decentralization and passing from a mode of individual to collective action are necessary conditions for a conception of an actually innovative educational management, one that overcome the mere focus on administration. The outcome highlights the centrality of the human element in the construction of an organization of the school and of education, pointing internal communication as a management strategy in the context of the educational systems and schools.
Keywords: Comunicação interna; Gestão educacional; Pesquisa-ação; Estratégia; Internal communication; Educational management; Research-action; Strategy; ACCNPQ::Ciências Humanas::Educação